Fundusze Unii Europejskiej jako źródło wsparcia podmiotów sektora mięsnego Polsce - Pondel, Hanna (The European Union Funds as a Source of the Polish Meat Sector Entities Support, 2005)
Selected the European Union funding sources of activity of the meat sector entities are presented in this article. The financial assistance is indispensable to many entities for enlargement of their market competitiveness. The European Union finance enables farmers and food processing companies to achieve adequate sanitary, veterinary and environmental standards, adapt the offer to market needs (with reference to the assortment and the quality) and initiate the technological and biological progress. Polish farmers and food processing companies can use the European Union's finance on the wide range without spending little money on their instruction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 224-228